2005
DOI: 10.1097/01.sle.0000160289.01159.0e
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Surgical Simulation With Attention to Validation Methodology

Abstract: The use of simulation technology for teaching and evaluating surgical skills has gained considerable attention in recent years. This is driven by interest in quality of care, concerns over increasing operative complexity, constraints on the use of animal models, limited available patient material, medicolegal pressures, and fiscal mandates for cost-effective performance. Traditional mechanical models are yielding to techniques dependent on electronic technology, including virtual reality. Data to support the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(34 citation statements)
references
References 37 publications
1
31
0
2
Order By: Relevance
“…Despite considerable improvement in individual skills outside the operating room with simulation, competence performing surgery in the operating room still is under investigation [26][27][28]. One reason is that the low fidelity of most simulations restrains trainees from transferring their lab skills to the clinical setting [29].…”
Section: Discussionmentioning
confidence: 99%
“…Despite considerable improvement in individual skills outside the operating room with simulation, competence performing surgery in the operating room still is under investigation [26][27][28]. One reason is that the low fidelity of most simulations restrains trainees from transferring their lab skills to the clinical setting [29].…”
Section: Discussionmentioning
confidence: 99%
“…Though there is no universal system to evaluate the surgical abilities precisely, there are three general categories identified for quality evaluation of the surgeon: (1) clinical cognitive abilities, (2) technical abilities, and (3) social interaction 4 . The graduation course must emphasize on methodologies that promote the active participation at the student educational process, early introducing him in practical activities indispensable for the medical career 5 .…”
Section: Discussionmentioning
confidence: 99%
“…With the summary of questionnaire, face and content validity were demonstrated. For a training model to be effective, construct validity, which distinguishes the level of training (19,20), has to be proved. In the present study, this was clearly demonstrated by comparing the results of experts with those of novices.…”
Section: Discussionmentioning
confidence: 99%